2002
DOI: 10.1002/app.11110
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and thermal characterization of high‐ and low‐density irradiated polyethylenes

Abstract: A comparative study of the dynamic mechanical relaxation spectra of high-and low-density polyethylenes irradiated with ␥-radiation from a Co 60 source was performed. The irradiation doses ranged from 0 to 100 Mrad. All the samples were previously characterized by determination of the molecular weight distribution, the number of functional groups, and the crystalline fraction. All the relaxation zones between Ϫ145°C and the melt were studied in the frequency range from 0.3 to 30 Hz. The changes observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
(25 reference statements)
2
3
0
Order By: Relevance
“…Considering the second scan, both the melting point and the crystalline content decrease with the radiation dose, although this effect is more prominent for lower radiation doses. These results are in agreement with the works of some authors,2, 5, 8, 10, 11, 20, 21 which have suggested that the decrease of the crystalline content and the melting point could be atributable to the increase of the imperfections in the polymeric chains originated by the radiation. These defects of the polymeric chains could inhibit the crystallization process, leading to smaller and less‐perfect crystallites.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Considering the second scan, both the melting point and the crystalline content decrease with the radiation dose, although this effect is more prominent for lower radiation doses. These results are in agreement with the works of some authors,2, 5, 8, 10, 11, 20, 21 which have suggested that the decrease of the crystalline content and the melting point could be atributable to the increase of the imperfections in the polymeric chains originated by the radiation. These defects of the polymeric chains could inhibit the crystallization process, leading to smaller and less‐perfect crystallites.…”
Section: Resultssupporting
confidence: 93%
“…As a whole, for the original irradiated samples before fractionation (s1, s2, s3, and s4), the vinyl and vinylidene ratios decrease with the radiation dose, whereas the transvinylene, ketone, and aldehyde ratios increase. Consequently, γ‐radiation promotes the formation of imperfections in the polymeric chains, in agreement with previous works 20, 21…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This phenomenon is attributed to the presence of the smaller chain segment, resulting from the bon scission in the backbone of the XLPE macromolecules at high temperatures. Chain scission was favorezed by oxidation process [5,6]. It is normally accepted that the degradation, though taking place mainly in the amorphous phase, may also occur at the lamellar fold surfaces, and causes an increase in the surface free energy of the crystals resulting in a reduction of the melting temperature [7].…”
Section: Resultsmentioning
confidence: 99%
“…The discussion is widened because of the possible presence of many processes in this relaxation and due to their localization. Many studies indicate that the mechanical and/or dielectric γ relaxation zone contains two or even more sub-relaxations of different origins, relaxation times and activation energies [22,53,[61][62][63][64][65]. According to Stehling et al [25] and Alberola et al [61,62], the γ relaxation is related to the glass transition, and for others, this relaxation can be regarded as a sub-glass transition attributed to the local motion of the central C-C bond of short chain segments (by crank-shaft [66] or flipflop mechanism [67]) and/or the local motion of loose chain ends in the amorphous phase [68].…”
Section: γ Relaxationmentioning
confidence: 99%